ASPECTS OF JAVANESE NUANCED POLITENESS WHEN SERVING HOTEL GUESTS IN YOGYAKARTA - Budi Purnomo (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
A receptionist is the first and the last person guests talk to in a hotel. If s/he makes a good impression with skillful services and good communication followed by other hotel staff, the guests have no reason to complain, and oppositely, they would come back again. This study aims to analyze aspects of Javanese politeness which is expressed by hotel receptionists during their communication with guests in Yogyakarta. Location of the research is Yogyakarta City, Indonesia. Data include four kinds of conversational discourse: (1) checking guests in, (2) providing guests with information, (3) dealing with guest complaints and (4) checking guests out. Techniques of collecting data include observation and field notes, recordings, questionnaire, in-depth interviewing and document analysis. The findings show that hotel receptionists in Yogyakarta use aspects of Javanese politeness on one occasion, but violate them on another occasion. The aspects of Javanese nuanced politeness they use and violate are sumanak ‘friendly’, sabar lan sareh ‘patient and with ease, calm’, tepa slira ‘showing a feeling of sympathy or solidarity’, andhap asor ‘giving a high respect, appropriate appreciation’, empan papan ‘matches with the setting and occasion’ and nuju prana ‘pleasing, satisfying’.